Using the Multidimensional Leadership Questionnaire to Analyse the Relationships Between Urban Leadership and the Attributes of Transactional and Transformational Leadership - Baran, Katarzyna; Mazur, Stanisław; Prokopowicz, Piotr (Journal of Public Governance, 2023)
Objectives: To analyse the relationships between urban leadership and the attributes of transactional leadershipand transformational leadership.Research Design & Methods: The analysis was performed using the Multidimensional Leadership Questionnairefrom 6th December, 2020, to 7th June, 2021. The surveyed sample comprised mayors of Polish cities, their deputies, and city secretaries (surveyed population: 111; sample size: 48).Findings: The findings demonstrate a significant link between the leadership behaviours of the mayors and more objective urban performance indicators as perceived by their direct subordinates. Focusing development efforts and activities on those behaviours that most strongly correlate with a wide range of performance indicators, such as idealised influence or contingent reward, may translate into an improved effectiveness of urban authorities. The study also emphasises the importance of maintaining a balance between a variety of leadership styles.Implications / Recommendations: Building theoretical models to explore the issue of urban leadership will becritical for future research on urban leadership. Equally essential will be the expanded use of psychometricindicators in the context of meta-analyses and theoretical models revealing the links that exist between leaderbehaviour and various performance metrics.Contribution / Value Added: The article’s added value is in providing evidence that multifaceted leadership, basedon transactional and transformational leadership traits, is required to ensure the quality of management of complex and dynamic systems, such as large cities.Article classification: empirical articleJEL classification: H1, H4, H7